Integration efforts in radical and incremental projects of new product development based on biodiversity: Case study in a biotechnology company - De Araújo, Tiago Ribeiro [UNESP]; Jugend, Daniel [UNESP] (FapUNIFESP (SciELO), 2016)
Recent research on new product development (NPD) has presented divergent results on the need for interfunctional integration efforts. Studies have shown that contingent ascpects and the level of innovation incorporated into product projects are elements that should be considered in these integration efforts. This study aimed to analyze how integration efforts occur in incremental and radical NPD projects. A case study was conducted in a company that continuously develops technologies and products based on Brazilian biodiversity. Among the main results, we noted that due to their greater technological complexity, the radical innovation projects require more intense integration. The physical distance from the R&D department was also shown to be a situation that generates positive results for the development of these types of projects. On the other hand, we observed that co-location is beneficial for interaction between the teams in the case of incremental innovation projects. The application of information technologies, such as Customer Relationship Management Systems as formal support mechanisms for integration in radical and incremental innovation projects was also observed.
Keywords: Biotechnology company; Case study; Innovation; Innovation management; Inter-departamental integration; New product development